Efficient Syntheses of Ethyl 2-Methylthio- and Ethyl 2-Benzylthio-6-methyl(aryl)pyrimidine-4-carboxylates and Their Carboxylic Acid Derivatives - Zanatta, Nilo; Fortes, Andressa S.; Bencke, Carlos E.; Marangoni, Mário A.; Camargo, Adriano F.; Fantinel, Cassio A.; Bonacorso, Helio G.; Martins, Marcos A. P. (Synthesis, 2015)
A simple and efficient procedure for the synthesis of ethyl 2-methylthio- and ethyl 2-benzylthio-6-methyl(aryl)-pyrimidine-4-carboxylates and their corresponding acid derivatives is reported. The products are obtained in good yields via the cyclocondensation reaction of ethyl 4-alkoxy-2-oxo-4-methyl(aryl)-but-3-enoates with 2-methylisothiourea sulfate or 2-benzylisothiourea hydrochloride, under mild, basic, aqueous conditions.
Keywords: 2,4,6-trisubstituted pyrimidines; 2-thiopyrimidines; ethyl pyrimidine-4-carboxylates; pyrimidine-4-carboxylic acids; cyclocondensation